2017
DOI: 10.1038/s41598-017-18446-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a CARM1 Inhibitor with Potent In Vitro and In Vivo Activity in Preclinical Models of Multiple Myeloma

Abstract: CARM1 is an arginine methyltransferase with diverse histone and non-histone substrates implicated in the regulation of cellular processes including transcriptional co-activation and RNA processing. CARM1 overexpression has been reported in multiple cancer types and has been shown to modulate oncogenic pathways in in vitro studies. Detailed understanding of the mechanism of action of CARM1 in oncogenesis has been limited by a lack of selective tool compounds, particularly for in vivo studies. We describe the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 45 publications
7
115
0
Order By: Relevance
“…Competitive assays with SAM cofactor and peptide substrate showed that 2a and 5a act To the best of our knowledge, EZM2302, TP-064, SKI-73 (www.thesgc.org/chemicalprobes/SKI-73) and their derivatives are the only selective and cell-active CARM1 inhibitors. (Drew et al, 2017;Nakayama et al, 2018) While the potency, selectivity, on-target engagement and potential off-target effects associated with these compounds have been examined in vitro and in cellular contexts as chemical probes, EZM2302, TP-064, SKI-73 are distinct by their molecular scaffolds and modes of interaction with CARM1 (www.thesgc.org/chemical-probes/SKI-73). (Drew et al, 2017;Nakayama et al, 2018) SKI-73 is a cofactor analog inhibitor embedding a N6'homosinefungin moiety to engage the SAM binding site of CARM1 in a cofactor-competitive, substrate-noncompetitive manner; EZM2302 and TP-064 occupy the substrate-binding pocket of CARM1 in a SAH-uncompetitive or SAM-noncompetitive manner.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Competitive assays with SAM cofactor and peptide substrate showed that 2a and 5a act To the best of our knowledge, EZM2302, TP-064, SKI-73 (www.thesgc.org/chemicalprobes/SKI-73) and their derivatives are the only selective and cell-active CARM1 inhibitors. (Drew et al, 2017;Nakayama et al, 2018) While the potency, selectivity, on-target engagement and potential off-target effects associated with these compounds have been examined in vitro and in cellular contexts as chemical probes, EZM2302, TP-064, SKI-73 are distinct by their molecular scaffolds and modes of interaction with CARM1 (www.thesgc.org/chemical-probes/SKI-73). (Drew et al, 2017;Nakayama et al, 2018) SKI-73 is a cofactor analog inhibitor embedding a N6'homosinefungin moiety to engage the SAM binding site of CARM1 in a cofactor-competitive, substrate-noncompetitive manner; EZM2302 and TP-064 occupy the substrate-binding pocket of CARM1 in a SAH-uncompetitive or SAM-noncompetitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…(Drew et al, 2017;Nakayama et al, 2018) While the potency, selectivity, on-target engagement and potential off-target effects associated with these compounds have been examined in vitro and in cellular contexts as chemical probes, EZM2302, TP-064, SKI-73 are distinct by their molecular scaffolds and modes of interaction with CARM1 (www.thesgc.org/chemical-probes/SKI-73). (Drew et al, 2017;Nakayama et al, 2018) SKI-73 is a cofactor analog inhibitor embedding a N6'homosinefungin moiety to engage the SAM binding site of CARM1 in a cofactor-competitive, substrate-noncompetitive manner; EZM2302 and TP-064 occupy the substrate-binding pocket of CARM1 in a SAH-uncompetitive or SAM-noncompetitive manner. (Drew et al, 2017;Nakayama et al, 2018) In particular, the prodrug property of SKI-73 allows its ready cellular uptake, followed by rapid conversion into its active forms inside cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations